2008
DOI: 10.1016/j.cellbi.2008.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose aspirin promotes endothelial progenitor cell migration and adhesion and prevents senescence

Abstract: Circulating endothelial progenitor cells (EPCs) play a key role in restoring endothelial function and enhancing angiogenesis. However, the effects of low-dose aspirin on circulating EPCs are not well known. We investigated the effects of low-dose aspirin on EPC migration, adhesion, senescence, proliferation, apoptosis and endothelial nitric oxide synthase (eNOS) expression. EPC migration was detected by a modified Boyden chamber assay. EPC adhesion assay was performed by counting adherent cells on fibronectin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 47 publications
(43 reference statements)
3
30
0
Order By: Relevance
“…The mechanism whereby ACEI promote TERT, in the present conditions, seems to be related to the activation of the FGF-2 pathway, because its silencing or neutralization abrogates TERT expression. Although the evidence indicating down-regulation of telomerase by oxidative stress is overwhelming (Haendeler et al, 2004;Voghel et al, 2008;Erusalimsky and Skene, 2009), interventions that favor its up-regulation are limited to NO donor drugs (Vasa et al, 2000), statins (Haendeler et al, 2004), low-dose aspirin (Hu et al, 2008), estrogen (Grasselli et al, 2008), and FGF-2 (Kurz et al, 2003). The direct stimulation of human TERT expression by NO, either endogenously produced or delivered by NO donor agents as shown here, has recently been disputed (Erusalimsky and Skene, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism whereby ACEI promote TERT, in the present conditions, seems to be related to the activation of the FGF-2 pathway, because its silencing or neutralization abrogates TERT expression. Although the evidence indicating down-regulation of telomerase by oxidative stress is overwhelming (Haendeler et al, 2004;Voghel et al, 2008;Erusalimsky and Skene, 2009), interventions that favor its up-regulation are limited to NO donor drugs (Vasa et al, 2000), statins (Haendeler et al, 2004), low-dose aspirin (Hu et al, 2008), estrogen (Grasselli et al, 2008), and FGF-2 (Kurz et al, 2003). The direct stimulation of human TERT expression by NO, either endogenously produced or delivered by NO donor agents as shown here, has recently been disputed (Erusalimsky and Skene, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Is there a possibility to tune EPCs in culture, so that their angiogenic potential is increased? In a recent study Hu et al investigated the effect of low-dose aspirin on the proliferation and the functional capacity of EPCs in cell culture (34). These experiments clearly demonstrated that aspirin up to a concentration of 10-100 lmol/L increased the migratory capacity of the cells without influencing the proliferation.…”
Section: Cell Culturementioning
confidence: 99%
“…AcLDL uptake and lectin binding have been used in a number of important EPC studies [13,14,15,16,17,18], and constitutes the necessary step in measuring culture EPC number [20]. Additional EPC markers are now recommended.…”
Section: Discussionmentioning
confidence: 99%
“…MNC (10 × 10 6 ) were seeded in 6-well plates coated with human fibronectin (BD BioCoat, Biosciences) in 3 ml of endothelial basal medium (Lonza) with supplements (EGM SingleQuots: 10 µg/ml hEGF, 1 µg/ml hydrocortisone, 3 µg/ml bovine brain extract, 30 µg/ml gentamicin, 50 µg/ml amphotericin B and 2% fetal bovine serum) as described previously [13,14,15,16,17,18]. After 4 days of culture, nonadherent cells were removed, and adherent cells were washed with phosphate buffer saline before adding 3 ml of fresh endothelial basal medium with supplements, and cultured for 3 days.…”
Section: Methodsmentioning
confidence: 99%